La nuova edizione del Piano Lauree Scientifiche - Cosentino, Ugo (Chimica nella Scuola, 2024)
The Piano Lauree Scientifiche has been implementing orientation actions for the continuation of university studies in the scientific field and activities aimed at the professional development of in-service teachers for more than fifteen years. These actions are carried out in close synergy with the other planned actions: the reduction of the university dropout rate, self-evaluation activities and laboratories for teaching basic sciences. These approaches offer numerous ideas also in the context of a renewal of university teaching.